Interfering women: farm mothers and the reproduction of family farming - O'Hara, Patricia (Economic & Social Studies, 1997)
The continuance of family farming in Ireland is dependent on family formation and reproduction which are processes in which women are central actors. Family farming as a social form is organised around gender-based work roles so that farm women have responsibility for the care and sustenance of the farm family through their responsibility for children and work in the home. Despite this, relatively little is known about farm women's involvement in the reproduction of family farming. In this paper farm women's involvement in the evolution of family farming and on the structure of Irish society is explored by examining their influence on the exceptional educational attainment of farm children. This means that the focus is on farm women in their role as mothers rather than as wives. This in turn, involves a shift away from the more conventional tendency to view the family farm as an arena of production only, to seeing it also as a site of reproduction.
Keywords: Family farming; Women in farming; Ireland